THYMIC SQUAMOUS CELL CARCINOMA - CASE REPORT AND DOCUMENTARY OVERVIEW (Vietnam Journal of Community Medicine, 2022)
Histopathological classification of thymic tumors 2015, WHO update 2021, thymic carcinomas aredivided into 3 large groups: Thymoma/benign thymic tumors; Thymic carcinoma/ Thymus cancer;Thymic neuroendocrine/ Neuroendocrine thymoma.Thymic carcinoma (Thymic Carcinoma - TC) accounts for 70% of cases of Thymoma; In which, thetype of squamous carcinoma (Thymic Squamous Cell Carcinoma -TSCC) is very rare, diagnosedbased on histopathology criteria and immunohistochemistry. Patients with TSCC also often haveclinical symptoms associated with mediastinal tumor: Invasion of intramediastinal structures iscommon, including superior vena cava syndrome; However, the common paraneoplastic syndromesin thymoma such as myasthenia gravis, erythrocytosis, and hypogammaglobulinemia are very rarein TSCC. TSCC has a very high malignancy and is often metastasized. The detection rate of distantmetastases is up to 50-65% at the time of diagnosis. Common sites of metastasis include lung, liver,brain, and bone. The prognosis for TSCC is very poor with a 5-year survival rate of 30%. The meanage at diagnosis was 50.We introduce a 70-year-old male patient, who came to the National Lung Hospital for examinationand treatment, was diagnosed with TSCC by histopathology and immunohistochemistry with adiagnostic approach to help colleagues industry for reference.
Keywords: Thymic Carcinoma, Thymic Squamous Cell Carcinoma, Immunohistochemistry.